Biomarkers of cardiovascular disease are increased in untreated chronic periodontitis: a case control study. (2014)
Background: The aim of this study was to evaluate the endothelial function, systemic inflammatory biomarkers and subgingival microbial profile associations in patients with and without periodontal disease.